Ideal dose intensity of R-CHOP in diffuse large B-cell lymphoma. Issue 6 (3rd June 2022) - Miura, Katsuhiro; Takahashi, Hiromichi; Nakagawa, Masaru; Hamada, Takashi; Uchino, Yoshihito; Iizuka, Kazuhide; Ohtake, Shimon; Iriyama, Noriyoshi; Hatta, Yoshihiro; Nakamura, Hideki
ABSTRACT: Introduction: The standard of care for diffuse large B-cell lymphoma (DLBCL) is rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP). However, its ideal dose intensity varies among cases. Areas covered: This review provides the latest insights on the dose intensity of R-CHOP for DLBCL patients. Specifically, we discussed the optimal dose intensity for elderly patients, the optimal number of treatment cycles for limited or advanced-stage diseases, and the role of dose-intensified therapies or adding targeted inhibitors. Expert opinion: Performing a comprehensive or simplified geriatric assessment can distinguish elderly DLBCL patients who will likely benefit from curative R-CHOP. Very elderly or medically unfit patients may need dose reduction in R-CHOP; the Age, Comorbidities, and Albumin index may aid decision-making. Four cycles of R-CHOP followed by two rituximab cycles comprise a new standard for low-risk, limited-stage DLBCL patients. Compared to eight cycles, six cycles of R-CHOP have similar efficacy and fewer toxicities for advanced-stage DLBCL. Dose-intensified therapy is not recommended in most DLBCL cases but may be considered for patients with double (or triple)-hit lymphoma. Applying targeted inhibitors and not merely escalating R-CHOP dose intensity through molecular subtyping will improve the treatment outcome for DLBCL. PLAIN LANGUAGE SUMMARY: Diffuse large B-cell lymphoma (DLBCL) is one of the most common blood cancers. Patients with DLBCL are usually treated with a standard (immuno-) chemotherapy called R-CHOP, which stands for rituximab, cyclophosphamide, hydroxydaunorubicin (doxorubicin), Oncovin, and prednisone. Of these, cyclophosphamide and doxorubicin are particularly toxic but effective. Therefore, the dosages of these drugs are adjusted according to the patient's body size. However, the ideal amounts of these drugs (dose intensity) can vary from case to case. For instance, the regular dose intensity of R-CHOP is too toxic for some people, such as very older patients. Furthermore, ideal total amounts of these drugs, that is, ideal cycle numbers of R-CHOP, are also different between patients with limited disease and advanced disease. Therefore, oncology/hematology researchers have been seeking the optimal dose intensity of R-CHOP in each patient with DLBCL for years. The goal of this review is to provide the latest insights on the ideal dose intensity of R-CHOP in DLBCL treatment. In this article, we discuss: how R-CHOP was established as the standard of care for DLBCL, how to identify candidates for standard R-CHOP among older patients, how to adjust the dose intensity of R-CHOP for patients who are not candidates for standard R-CHOP, optimal cycle number of R-CHOP for limited-disease DLBCL, optimal cycle number of R-CHOP for advanced DLBCL, how to treat patients with a large mass, and the role of more intensive therapies other than R-CHOP in DLBCL treatment. Finally, we demonstrate how experts determined the dose intensity of R-CHOP for some example cases with DLBCL.